2004
DOI: 10.1016/j.annepidem.2003.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Indoor allergens, asthma, and asthma-related symptoms among adolescents in Wuhan, China

Abstract: Indoor allergen exposures were positively associated with asthma diagnosis and persistent respiratory symptoms among Chinese adolescents. Neither early-life nor current exposure to animals was protective for asthma or asthma-related symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
37
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 59 publications
2
37
0
4
Order By: Relevance
“…The prevalence of allergies in Shanghai children is comparable to that in western countries [33] and is generally higher than for other Chinese cities [8,19,25,26]. This survey indicated that the prevalence of asthma in 4-6 years old children has risen to 10.3%, much higher than the 5.92% reported for Shanghai 6-14 year old children in 2007 [34].…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…The prevalence of allergies in Shanghai children is comparable to that in western countries [33] and is generally higher than for other Chinese cities [8,19,25,26]. This survey indicated that the prevalence of asthma in 4-6 years old children has risen to 10.3%, much higher than the 5.92% reported for Shanghai 6-14 year old children in 2007 [34].…”
Section: Discussionmentioning
confidence: 56%
“…Although pet-keeping might increase sensitization, it could alleviate the degree of the symptoms-development [1] and prevent children from getting hay fever [6]. Some studies have shown that there were no significant associations between pet-keeping and allergies in childhood [7][8][9] or a "protective" effect on early pet-keeping [4,[10][11][12][13][14][15][16]. But some other studies revealed that the "protective" effect might be confounded by parental avoidance behavior or selection of particular pet species [10,16,17].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…La relación entre exposición a animales domésticos y el desarrollo de enfermedades respiratorias alérgicas en la niñez es controvertida. Aunque algunos estudios han mostrado que la exposición a estos alérgenos se asocia con prevalencia de asma y exacerbaciones de la enfermedad 26,27 , otros estudios sugieren que la exposición temprana a estos animales puede reducir el riesgo de desarrollar síntomas alérgicos, asma y sibilancias 28,29,30,31,32 . En este sentido se ha propuesto la teoría de que altas exposiciones a productos microbianos, como endotoxinas bacterianas, a edades tempranas puede mediar inmunológica-mente este efecto protector, especialmente en áreas metropolitanas 33,34,35 .…”
Section: Discussionunclassified
“…En este tema, diversos estudios han demostrado la asociación de contaminantes domiciliares, como hongos, ácaros, cucarachas, combustibles de biomasa y humo de cigarrillo, entre otros, con la presencia de morbilidad respiratoria, especialmente en niños, que permanecen la mayor parte del tiempo en sus casas (25)(26)(27)(28)(29)(30)(31)(32).…”
Section: Discussionunclassified